NUTRITIONAL STATUS, NUTRIENT INTAKES AND PHYSICAL ACTIVITY IN RELATION TO PHYSICAL FITNESS - Mustakim, Mustakim; Ahmad, Kusdinar (Universitas Ahmad Dahlan, 2016)
Background: The study focused on the physical fitness of Senior High School?s students at Sragen, Central Java in 2010. The purpose of this study was to determine the relations between nutritional status, nutrient intakes, and physical activity to physical fitness measured by fitness test using Indonesia?s Physical Fitness Test for aged 16-19 years minus pull-up test. Method: This study was a cross-sectional design. The data was collected from 198 Senior High School?s students at Sragen; Central Java aged 16-19 years. Result: The result showed that 63.6 percentage of respondent belonged to the weak condition. Sports activity and sex were significantly related to physical fitness. Conclusion: The researcher suggests that students should keep their sports activity goes on in the regular and active condition especially for female students.